Perbandingan Strategi Pembelajaran Konvesional dan Digital dalam Pembelajaran Jarak Jauh - Rahmatul Zikri Amalia; Selvi Yulianis; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2025)
The world of education has undergone a major shift as a result of advances in information and communication technology. This study compares conventional and digital learning methods for distance learning (PJJ) across the board, with the aim of finding out what is effective, what is not effective, and how the two methods affect student learning outcomes and experiences. Conventional learning, which relies on direct interaction between teachers and students, emphasizes elements such as giving feedback, easy to do, structured, and routine. It has the advantage of being able to facilitate direct interpersonal communication, provide intensive supervision and guidance, and create a competitive learning environment. However, this method has some limitations, especially in terms of time and space flexibility. It is also not able to meet the learning needs of individuals in large groups. On the other hand, digital learning offers greater flexibility, access to a wide range of educational resources, and increased interactivity through the use of online collaboration tools, e-learning platforms, and video conferencing. The use of technology allows learning content to be presented in a systematic, structured and engaging manner, increasing student motivation and participation. In addition, it allows materials to be tailored to each student's learning style and conditions, and supports collaborative and independent learning. Challenges include the possibility of misuse of technology, limited access in some areas, lack of direct social interaction, and reliance on digital infrastructure and capabilities. The research results indicate that digital learning generally enhances student learning outcomes more significantly compared to conventional learning, especially in terms of distance learning (PJJ). Digital strategies such as structured instructional design, integration of practical experiences, motivational support, and time management have been shown to improve student interaction, understanding, and independence. However, digital and conventional learning methods can complement each other to achieve optimal effectiveness. The application of these strategies not only boosts students' academic performance but also equips them with the essential skills to tackle future challenges.